A critical analysis of the Malaysian risk-based capital framework: A comparison between general insurance and takaful - Yusof, Aida Yuzi; Lau, Wee Yeap; Osman, Ahmad Farid (Faculty of Economics and Administration, University of Malaya, 2016)
This paper aims to critically analyse the Malaysian solvency system by comparing the existing Risk-Based Capital (RBC) framework for Conventional and Takaful against the seven specific objectives of the original US Risk-Based Capital which was introduced in 1994. In addition, the Malaysian Risk-Based Capital framework is also assessed against the four extended objectives developed by Holzmüller in 2009. The critical evaluation results indicate that the Malaysian Conventional and Takaful Risk-Based Capital frameworks have various shortcomings from both qualitative and quantitative aspects. The framework only fully meets three out of seven objectives of the US Risk-Based capital framework and fulfils one out of four additional objectives developed in 2009: Malaysia’s Risk-Based Capital framework only fulfils the following: the appropriate incentive for capital expansion, measurement of economic values of assets and liabilities, sound financial reporting and assessment of management. As a consequence, it is clear that the current one-size-fits-all approach must be reviewed to improve the Malaysian RBC Framework in view of different sizes and assets of existing firms in the industry.